Quantifying instantaneous performance in alpine ski racing - Federolf, P. A. (Journal of Sports Sciences, 2012)
Alpine ski racing is a popular sport in many countries and a lot of research has gone into optimising athlete performance. Two factors influence athlete performance in a ski race: speed and the chosen path between the gates. However, to date there is no objective, quantitative method to determine instantaneous skiing performance that takes both of these factors into account. The purpose of this short communication was to define a variable quantifying instantaneous skiing performance and to study how this variable depended on the skiers' speed and on their chosen path. Instantaneous skiing performance was defined astime loss per elevation difference dt/dz, which depends on the skier's speed v(z), and the distance travelled per elevation difference ds/dz. Using kinematic data collected in an earlier study, it was evaluated how these variables can be used to assess the individual performance of six ski racers in two slalom turns. The performance analysis conducted in this study might be a useful tool not only for athletes and coaches preparing for competition, but also for sports scientists investigating skiing techniques or engineers developing and testing skiing equipment.